Revitalisasi Kegiatan Bulan Kitab Suci Nasional Melalui Pendekatan Pastoral dan Teologi Sabda di Stasi Riung - Maria Margareta Masa Baodai; Hermania Bhoki (PELITA NUSA TENGGARA, 2026)
National Bible Month (BKSN) is a pastoral program of the Catholic Church aimed at fostering the faithful’s love for the Holy Scriptures as the source of faith and life guidance. However, the implementation of BKSN in Riung Station has not been fully effective due to low community participation, less varied reflection methods, and limited contextual understanding of the Word of God in daily life. This activity aimed to revitalize the implementation of BKSN through a pastoral and Theology of the Word approach in order to make it more participatory and contextual. The program was carried out as part of the Community Service Program (KKN) using pastoral assistance, contextual Bible reflections, group discussions, and communal faith-sharing methods. The results showed increased community participation, greater interest in reading the Scriptures, and a deeper understanding of the Word of God in relation to daily life. This activity contributes to strengthening the faith life of the community and encouraging the sustainability of Bible reflection activities in Riung Station.